Common Variants in PLXNA4 and Correlation to CSF-related Phenotypes in Alzheimer's Disease - Han, Qiu; Sun, Yong-An; Zong, Yu; Chen, Chun; Wang, Hui-Fu; Tan, Lan; , Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2018)
Plexin-A 4 (PLXNA4) gene has been identified as a novel genetic player to associate with Alzheimer’s disease (AD) in recent genome wide association studies (GWAS). Besides, PLXNA4 genetic variations were found to increase AD risk by tau pathology in vitro. However, the potential roles of PLXNA4 variants in AD were not evaluated. Five targeted loci capturing the top of common variations in PLXNA4 were extracted using tagger methods. Multiple linear regression models were used to explore whether these variations can affect cerebrospinal fluid (CSF) (Aβ1-42, T-tau, and P-tau) phenotypes in the Alzheimer’s disease Neuroimaging Initiative (ADNI) dataset. We detected that two loci (rs6467431, rs67468325) were significantly associated with CSF Aβ1-42 levels in the hybrid population (rs6467431: P = 0.01376, rs67468325: P = 0.006536), the significance still remained after false discovery rate (FDR) correction (rs6467431: Pc = 0.03441, rs67468325: Pc = 0.03268). In the subgroup analysis, we further confirmed the association of rs6467431 in the cognitively normal (CN) subgroup (P = 0.01904, Pc = 0.04761). Furthermore, rs6467431-A carriers and rs67468325-G carriers showed higher CSF Aβ1-42 levels than non-carriers. Nevertheless, we did not detect any significant relationships between the levels of T-tau, P-tau and these PLXNA4 loci. Our findings provided preliminary evidences that PLXNA4 variants can confer AD risk through modulating Aβ deposition.